Measuring investment in human capital formation: An experimental analysis of early life outcomes - Orla Doyle; Colm Harmon; James J. Heckman; Caitriona Logue; Seong Hyeok Moon (University College Dublin, UCD School of Economics, 2013)
The literature on skill formation and human capital development clearly demonstrates that early investment in children is an equitable and efficient policy with large returns in adulthood. Yet little is known about the mechanisms involved in producing these long-term effects. This paper presents early evidence on the nature of skill formation based on an experimentally designed, five-year home visiting program in Ireland targeting disadvantaged families - Preparing for Life (PFL). We examine the impact of investment between utero to 18 months of age on a range of parental and child outcomes. Using the methodology of Heckman et al. (2010a), permutation testing methods and a stepdown procedure are applied to account for the small sample size and the increased likelihood of false discoveries when examining multiple outcomes. The results show that the program impact is concentrated on parental behaviors and the home environment, with little impact on child development at this early stage. This indicates that home visiting programs can be effective at offsetting deficits in parenting skills within a relatively short timeframe, yet continued investment may be required to observe direct effects on child development. While correcting for attrition bias leads to some changes in the precision of estimates, overall the results are quite similar.
Keywords: C12; C93; J13; J24; 330; Early childhood intervention; human capital development; randomized control trial; multiple hypotheses; permutation testing; Bildungsinvestition; Messung; Geburt; Kinder; Gesundheit; Irland